Pengelolaan dan Kepemimpinan Sekolah Katolik: Studi pada Sekolah-sekolah di KAM: Catholic School Management and Leadership: A Study of Schools in KAM - Dionisius Sihombing; Parno Sumanro Mahulae; Muammar Rinaldi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to explore and analyze the management and leadership in Catholic schools under the auspices of the Archdiocese of Medan (KAM). Using a quantitative descriptive approach, this study collected data from 280 respondents consisting of principals, teachers, and administrative staff in various Catholic schools in the KAM area. The assessment was carried out based on key standards that include the ability of school administrators to make decisions, the quality of leadership in realizing the school's mission and vision, and relations with Church authorities. The results showed that the majority of respondents felt that Catholic schools in KAM had generally met the standards of good leadership and management. As many as 34.9% of respondents considered that school administrators were able to make effective decisions, and 36.7% stated that school leadership had succeeded in implementing the school's mission and vision. However, several areas needed improvement, such as relations with Church authorities, where 40.8% of respondents felt that this relationship was inadequate. This study highlights the strengths and weaknesses in the management and leadership of Catholic schools in KAM. With continuous improvement in these aspects, these schools can continue to make positive contributions to quality education and student character development in North Sumatra.